Stunting-Free Playgroup as an Effort to Address Stunting in the Suku Anak Dalam (SAD) Community in Jambi Through Community Empowerment and Early Stimulation - Aulia, Hanifah Nurul; Sari, Ceria Permata (BKM Public Health and Community Medicine, 2024)
Purpose: The aims of this program initiation is to reduce the prevalence of stunting, improve the health and development of toddlers by considering the cultural and traditional specificities of the Suku Anak Dalam (SAD) community, and strengthen the community's self-reliance and sustainability. Methods: The stunting-free playgroup program was developed in response to the high stunting rate in Jambi, which was 18.0%, according to SSGI 2022. The SAD community residing in the forests of Jambi significantly contributes to this rate, with stunting prevalence reaching 40%. The unique characteristics of the SAD community, such as limited knowledge of nutrition and health, semi-nomadic lifestyle, and reliance on hunting and gathering, influence the stunting rates. The program involved forming a stunting-free playgroup to address stunting through child playtime, nutritional education sessions, child health care, and developmental stimulation. Results: The stunting-free playgroup initiative provided enjoyment for children and raised awareness and knowledge about the importance of proper child care among the SAD community. The program's target included parents and toddlers, engaging them in activities that empowered the community by training them to monitor growth and development independently. This approach improved family and community welfare while reinforcing the traditional culture and values of the SAD community. Conclusion: The program was conducted through cross-sector collaboration, involving traditional leaders, nutritionists, midwives, and early childhood education teachers, and it utilized local potential with community empowerment. This comprehensive approach is expected to address stunting in the SAD community effectively.